Estimates of Genetic Variability in a Collection of Amaranths (Amaranthus ssp) Cultivated in Burkina Faso - Jacques, Ouedraogo; Zakaria, Kiébré; Pingawindé, Sawadogo; Nikodème, Kabré Vonogo; Mariam, Kiébré; Pauline, Bationo Kando (European Scientific Journal, ESJ, 2022)
In Burkina Faso, little information is available on morphological variability of amaranth and the association of different genetic traits. This has been a constraint to its genetic improvement for yield potential, whereby the necessity of this study which aimed at assessing 80 accessions of amaranth collected in the three agro-climatic zones of Burkina Faso. The study was conducted in 2019 during the rainy season. The experimental design was a Randomized complete block design (RCBD) with three replicates. A total of 12 quantitative descriptors related to the vegetative system, flowering cycle, and leaf and seed yield were assessed. The level of variation of each descriptor, their correlations, and their importance in the structure of agro-morphological variability of amaranths was studied. Significant morphological variability was observed among the accessions. The most discriminating and heritable traits were leaf blade length, number of primary branches bearing an inflorescence, number of leaves per plant, and fresh leaf weight. Late maturing accessions with many branches and long leaves were the best accessions for leaf biomass production. Early maturing accessions with fewer primary branches had better seed production. Two accessions, namely BOB4 and BOB5 of Amaranthus hypochondriacus were identified as the best seed yielding. Breeding programs to facilitate parental selection and increase genetic diversity in breeding populations can use these data.